Criminal justice participation among Japanese adults: a preliminary study - Mukai, Tomoya (International journal of law, crime and justice, 2023)
A growing number of studies have argued that public participation in criminal justice has become increasingly important in recent years; however, empirical data on the prevalence and determinants of participation in criminal justice are limited. Therefore, this study conducted a preliminary exploration of the prevalence and determinants of criminal justice participation experience and intention using data from 848 Japanese adults. This study defined the concept of criminal justice participation based on the notion of political participation used in political sciences. The results demonstrated that only 10.5% of the respondents had experienced at least one of the nine examined activities (e.g., participating in demonstrations and posting their thoughts on SNS). In addition, the mean of each intention item ranged from 1.46 to 2.04 on a five-point Likert scale. Moreover, experience and intention were not significantly affected by demographic variables, except for gender, with men showing higher experience and intention to participate.